An Embedded Cloud Design for Internet-of-Things - Teemu Laukkarinen; Jukka Suhonen; Marko Hännikäinen (International Journal of Distributed Sensor Networks)
Internet-of-Things (IoT) consists of interconnected heterogeneous devices that ubiquitously interact with physical world. The devices are often resource constrained in terms of energy, computation, and communication resources. Distributing processing between these heterogeneous devices could yield to better performance and sharing, and extending resources of the devices could yield to more intelligent ubiquitous applications. Such a design can be called as “embedded cloud”, which is defined in this paper. An embedded cloud design is presented that consists of distributable Process Description Language (PDL), Distributed Middleware (DiMiWa), and an infrastructure. As a result, PDL can execute distributed processes and share resources as services over heterogeneous IoT devices with help of DiMiWa and the infrastructure. The design is evaluated with a prototype implementation, where PDL and DiMiWa are executed on a small 8-bit microcontroller-based IoT device. The implementation requires only 5122 B of program memory (4% of the available), consumes under 1 ms of CPU time per process in the worst case, and allows over 100 simultaneous services per device.